Evaluation of primary lateral neck mass in adults: Cross sectional study - Limardo, Andres Constantino; Blanco, Luis; Menendez, Jose; Ortega, Adrian (Journal of Surgery and Medicine, 2020)
Aim: Primary Lateral neck mass (PLNM) is a disease that expresses a pathology in neck, excluding thyroid and skin tumors. The spectrum ranges from “lumps, mass or tumors,” congenital tumors, inflammatory diseases, and benign neoplasm to malignant neoplasm. The current Skandalakis algorithm excludes thyroid pathology. Correct anamnesis and physical examination are especially important for data collection. We herein analyzed the methods of study in PLNM. Methods: This cross-sectional study was performed with review of medical records from January 2010 to July 2019. All patients with diagnoses of PLMN and older than 15 years of age were analyzed. We excluded patients with “classic” and unknown lateral neck masses. Standardized protocols for data collection were implemented to minimize or avoid bias. The statistical analysis was carried out with STATA v 14.0. Results: A total of 78 patients were studied. Age and time of evolution were the most crucial factors in presumptive diagnoses. The most frequent location was the anterior triangle in the neck (77%). Murmurs and thrills were clinically defined as vascular pathologies. Mobility on all axes without fixation to deep planes were clinically defined as Lipoma. The pathological examinations were more frequently reported as lymphomas (32), which were followed by Branchial Cleft Cysts. Ultrasound was a complementary study useful in congenital malformations to determine cystic characteristics. The presence of “B symptoms” and FNA (fine needle aspiration) are useful in primary Lymphoproliferative adenopathy. MRI (Magnetic resonance image) and Angio-MRI are useful in tumors of nervous origin (schwannomas, neurofibromas, and paragangliomas tumors). Malignant soft tissue tumors (sarcomas) need complementary studies and imaging for surgical planning. Conclusion: Differential diagnoses of the primary lateral neck masses challenge surgeons. Anamnesis and physical examination are the most crucial factors for the presumptive diagnoses. Complementary studies and imaging should be requested with selective criteria.